Analysis of the modernity, effectiveness and safety of two industrial cutting machines - Kevin, Tsapi T; Desire, Soh Fotsing B.; Kenmeugne, Bienvenu (Journal Industrial Servicess, 2025)
In the face of global competition and technological advancements, modernizing industrial equipment is critical for enhancing productivity and safety in manufacturing. To explore this issue, this study assessed the modernity, effectiveness, and safety of two industrial cutting machines—a power hacksaw and a band saw—in the context of planned organizational changes to improve technological competitiveness. The study used several metrics, including the ABC technology method, Overall Equipment Effectiveness (OEE), and occupational safety levels derived from operator interviews, direct observation, and historical data analysis. The McKinsey matrix was used to summarize the findings. The results showed that both machines were below modern standards, with technology levels of 2.5 (power hacksaw) and 2.4 (band saw) on a 5-point scale. OEE measurements revealed performance gaps, with the band saw and power hacksaw operating at 65.5% and 71% of their full potential, respectively. Occupational safety levels were moderate at 3–3.2 on a 5-point scale, indicating a relatively low risk of accidents. The McKinsey matrix scores (290 and 320 out of 650) further highlight the lack of market competitiveness of the machinery. The study, limited to two small and medium-sized manufacturing companies in Bamenda, Cameroon, where reliance on outdated technology persists, underlines the need for modernization and improved equipment to increase productivity and safety. It contributes to the discourse on Africa's manufacturing challenges by suggesting actionable metrics for moving the sector forward.